Prediction of Poor Outcome Using the Urea to Albumin Ratio in Thoracic Empyema - Evgeni Dimitrov; Daniel Valchev; Georgi Minkov; Emil Enchev; Yovcho Yovtchev (Acta Medica Lituanica)
Purpose: The prognostic performance of urea-to-albumin ratio (UAR) has been assessed in various pulmonary and nonpulmonary conditions, but never in thoracic empyema. Therefore, our aim was to determine whether this marker has the ability to predict outcome in such patients. Methods: A single-center retrospective study was conducted in a Clinic of Thoracic Surgery at a University Hospital between January 2021 and October 2023. A total of 84 patients who underwent emergency surgery due to thoracic empyema were involved. Serum levels of urea and albumin at admission were used to calculate UAR. We analyzed area under receiver operating characteristics (AUROC) curves of UAR, systemic inflammatory response syndrome (SIRS) and quick-sequential organ failure assessment (qSOFA), and compared their prognostic performance. Results: The identified in-hospital mortality was 10.7%. The UAR showed the best ability to prognosticate mortality compared to qSOFA (AUROC = 0.828 vs 0.747) and SIRS (AUROC = 0.828 vs 0.676). We established a sensitivity of 87.5% and specificity of 74.2% at optimal cut-off value UAR > 51.1 for prediction of adverse outcome. Conclusion: In patients with thoracic empyema urea-to-albumin ratio showed significant prognostic performance and a potential for clinical application as a low cost and widely available predictor of death.